2022
DOI: 10.3389/fpsyg.2022.1049925
|View full text |Cite
|
Sign up to set email alerts
|

Online taxi users' optimistic bias: China youths' digital travel and information privacy protection

Abstract: Digital travel platforms not only provided people with convenient travel but also raised a series of problems regarding information privacy protection. In order to analyze privacy protection behavior, this study surveyed 441 subjects aged 18–35 who utilized digital travel platforms based on a structural model of protective motivation theory. The results indicated that a perceived threat, self-efficacy, and response efficacy positively and significantly impacted youths' privacy concerns. Furthermore, privacy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…As previously discussed, subjective privacy literacy primarily reflects self-efficacy and has more influence on the coping appraisal process rather than the threat appraisal process, which may explain its lack of direct association with privacy concern. Moreover, the results of this study indicate that privacy concerns positively predict privacy protection behaviors, corroborating the findings of Youn (2009) , Feng and Xie (2014) , Chen et al (2017) , Xie and Karan (2019) , and Meng and Feng (2022) , suggesting that users who express higher levels of privacy concerns are more inclined to engage in privacy protection behaviors.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As previously discussed, subjective privacy literacy primarily reflects self-efficacy and has more influence on the coping appraisal process rather than the threat appraisal process, which may explain its lack of direct association with privacy concern. Moreover, the results of this study indicate that privacy concerns positively predict privacy protection behaviors, corroborating the findings of Youn (2009) , Feng and Xie (2014) , Chen et al (2017) , Xie and Karan (2019) , and Meng and Feng (2022) , suggesting that users who express higher levels of privacy concerns are more inclined to engage in privacy protection behaviors.…”
Section: Discussionsupporting
confidence: 84%
“… Xie and Karan’s (2019) research found that privacy concerns about WeChat applications among college students had a significant and positive impact on their adoption of privacy protective behaviors. Similarly, Meng and Feng’s (2022) study confirmed that users of digital tourism platforms with higher privacy concerns were more likely to exhibit privacy protective behaviors. Based on the above analysis, it can be inferred that privacy literacy has the potential to enhance users’ privacy concerns, and these concerns, in turn, can further promote the adoption of privacy protective behaviors.…”
Section: Literature Review and Theoretical Hypothesessupporting
confidence: 66%
“…When medical data is improperly collected and misused, privacy concerns may arise, leading to a reluctance to disclose information and hindering the further adoption of mHealth. To examine the antecedents of information disclosure intention, current studies usually apply the integration framework of privacy calculus theory (Mohammed and Tejay, 2021;Wang et al, 2020), protection motivation theory (Meng and Feng, 2022;Chang et al, 2022), construal level theory (Li and Guo, 2022;Zhang et al, 2020), and technology acceptance model (Dhagarra et al, 2020;Sharif et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To examine the antecedents of information disclosure intention, current studies usually apply the integration framework of privacy calculus theory (Mohammed and Tejay, 2021; Wang et al. , 2020), protection motivation theory (Meng and Feng, 2022; Chang et al. , 2022), construal level theory (Li and Guo, 2022; Zhang et al.…”
Section: Introductionmentioning
confidence: 99%